Oxysterols: An emerging class of broad spectrum antiviral effectors. (June 2016) - Lembo, David; Cagno, Valeria; Civra, Andrea; Poli, Giuseppe
Abstract: Oxysterols are a family of cholesterol oxidation derivatives that contain an additional hydroxyl, epoxide or ketone group in the sterol nucleus and/or a hydroxyl group in the side chain. The majority of oxysterols in the blood are of endogenous origin, derived from cholesterol via either enzymatic or non-enzymatic mechanisms. A large number of reports demonstrate multiple physiological roles of specific oxysterols. One such role is the inhibition of viral replication. This biochemical/biological property was first characterised against a number of viruses endowed with an external lipid membrane (enveloped viruses), although antiviral activity has since been observed in relation to several non-enveloped viruses. In the present paper, we review the recent findings about the broad antiviral activity of oxysterols against enveloped and non-enveloped human viral pathogens, and provide an overview of their putative antiviral mechnism(s).